Shaping and enhancing resilient forests for a resilient society - Elena Cantarello; Jette Bredahl Jacobsen; Francisco Lloret; Marcus Lindner (Ambio, 2024)
The world is currently facing uncertainty caused by environmental, social, and economic changes and by political shocks. Fostering social-ecological resilience by enhancing forests’ ability to provide a range of ecosystem services, including carbon sequestration, habitat provision, and sustainable livelihoods, is key to addressing such uncertainty. However, policy makers and managers currently lack a clear understanding of how to operationalise the shaping of resilience through the combined challenges of climate change, the biodiversity crisis, and changes in societal demand. Based on a scientific literature review, we identified a set of actions related to ecosystem services, biodiversity conservation, and disturbance and pressure impacts that forest managers and policy makers should attend to enhance the resilience of European forest systems. We conclude that the resilience shaping of forests should (1) adopt an operational approach, which is currently lacking, (2) identify and address existing and future trade-offs while reinforcing win–wins and (3) attend to local particularities through an adaptive management approach.